Detecting Volcano‐Related Underground Mass Changes With a Quantum Gravimeter. Issue 13 (29th June 2022) - Antoni‐Micollier, Laura; Carbone, Daniele; Ménoret, Vincent; Lautier‐Gaud, Jean; King, Thomas; Greco, Filippo; Messina, Alfio; Contrafatto, Danilo; Desruelle, Bruno
Abstract: We present the world's first time series acquired in the summit area of an active volcano with an absolute atom interferometry gravimeter. The device was installed ∼2.5 km from the active craters of Mt. Etna volcano and produced a continuous high–quality gravity time series, despite the unfavorable environmental conditions at the installation site and the occurrence of phases of high volcanic tremor during the acquisition interval. Comparison with data from superconducting gravimeters installed elsewhere on Mt. Etna highlights correlated anomalies, demonstrating that the quantum device measured gravity variations driven by bulk mass changes. The latter are reflective of volcanic processes, involving the dynamics of magma and exsolved gas in the upper part of Mt. Etna's plumbing system. Our results confirm the operational possibilities of quantum gravimetry and open new horizons for the application of the gravity method in geophysics. Plain Language Summary: Mass redistributions occurring in the Earth's interior, for example, when a magma batch is displaced through the feeding system of an active volcano, may induce tiny changes in gravity over time, measurable on the ground. Measurement of such changes requires high‐precision devices, namely, the gravimeters, which can detect variations as small as one part in 10 9 of the gravity acceleration on Earth. However, standard gravimeters are not ideally suited for use in harsh field conditions, especially when continuous measurements are the target. Recent advances in quantum technology have allowed the development of a portable gravimeter which can successfully operate under field conditions. Here we present the world's first application of this quantum gravimeter for monitoring and studying an active volcano. The device was deployed only 2.5 km away from the summit active craters of Mt. Etna volcano (Italy) and has provided a high‐quality gravity time series. Inspection of this time series highlighted gravity changes which are reflective of bulk volcanic processes, involving magma and exsolved gas in the upper part of Mt. Etna's plumbing system. Key Points: We present the world's first time series acquired with an absolute quantum gravimeter in the summit crater zone of an active volcano Despite the unfavorable ambient conditions, the quantum gravimeter produced high quality data, allowing to track volcano‐related changes Comparison with the data from other gravimeters highlights changes due to bulk mass redistributions within Mt. Etna's feeding system